The Semiotics of Romantic Pain: A Barthesian Analysis of Selected Lyrics in Arctic Monkeys' "505" - Ida Fauziah Harwan; Muhammad Hasbi (Innovations in Language Education and Literature, 2026)
This study investigates how romantic pain and nostalgia are semiotically constructed in the lyrics of Arctic Monkeys' "505," employing Roland Barthes' three-level framework of denotation, connotation, and myth as its primary analytical lens. Five linguistically rich expressions were selected from the song; "505," "the knife," "fall short of the mark," "the bite," and "crumble completely", and examined as discrete semiotic units through a qualitative descriptive approach informed by Miles et al.'s (2014) analytical model. The analysis reveals that each expression moves systematically from a literal, accessible meaning at the denotative level, through emotionally layered connotations of longing, fear, inadequacy, and vulnerability, to mythological meanings that naturalize these experiences as universal and culturally inevitable features of romantic life. Collectively, the findings suggest that the song constructs romantic experience not as a condition of joy but as one defined by the emotional weight of memory, unspoken expectation, and the dissolution of self in intimate attachment. These results affirm that popular song lyrics function as culturally embedded semiotic texts capable of encoding and reproducing shared ideological constructions of human emotional experience.